The Phytochemical Bergenin Enhances T Helper 1 Responses and Anti-Mycobacterial Immunity by Activating the MAP Kinase Pathway in Macrophages - Dwivedi, Ved P.; Bhattacharya, Debapriya; Yadav, Vinod; Singh, Dhiraj K.; Kumar, Santosh; Singh, Mona; Ojha, Durbadal; Ranganathan, Anand; Van Kaer, Luc; Chattopadhyay, Debprasad; Das, Gobardhan (Frontiers in Cellular and Infection Microbiology, 2017)
Tuberculosis (TB) remains one of the greatest health concerns worldwide, which has hindered socioeconomic development in certain parts of the world for many centuries. Although current TB therapy, “Directly Observed Treatment Short-course,” is effective, it is associated with unwanted side effects and the risk for the generation of drug-resistant organisms. The majority of infected individuals successfully confine the mycobacterial organisms and remain asymptotic unless immune responses are perturbed. Thus, host immunity can protect against TB and immunomodulation is therefore an attractive therapeutic option. Previous studies have shown that TNF-α and Nitric Oxide (NO) in conjunction with IFN-γ-producing T helper 1 (Th1) cells play critical roles in host protection against TB. Here, we show that bergenin, a phytochemical isolated from tender leaves of Shorea robusta, activates the MAP kinase and ERK pathways and induces TNF-α, NO and IL-12 production in infected macrophages. We further show that bergenin induces Th1 immune responses and potently inhibits bacillary growth in a murine model of Mycobacterium tuberculosis infection. These findings identify bergenin as a potential adjunct to TB therapy.